PROFILE OF NOTIFIED CASES OF CONGENITAL SYPHILIS - Kátia Fernanda Alves Moreira; Davisson Michetti de Oliveira; Lucas Noronha de Alencar; Daniela Ferreira Borba Cavalcante; Aldrin de Sousa Pinheiro; Nathalia Halax Orfão (Cogitare Enfermagem, 2017)
The present study analyzed the incidence of congenital syphilis, tests for diagnosis, and treatment provided to newborns.This was a retrospective and descriptive epidemiological study with a quantitative approach.Data collection occurred in December 2015 using data from the Notifiable Diseases Information System provided by the Epidemiological and Environmental Surveillance Department of the Municipal Health Department of Porto Velho.The incidence of congenital syphilis increased during the period studied (2009 to 2014), from 0.92 cases to 8.65 per 1,000 live births.Regarding pregnant women, 157 (79.29%) carried out prenatal care, 119 (60.10%) were diagnosed during prenatal care, and 109 (55.1%) underwent inappropriate treatment.With regard to newborns, 99 (50.00%) were female, 126 (63.64%) were brown, 153 (77.27%) were born asymptomatic, and 129 (65.15%) were treated with crystalline penicillin G.Therefore, there are challenges regarding early diagnosis and appropriate treatment of pregnant women, their partners, and newborns in the city of Porto Velho.